2006
DOI: 10.1111/j.1464-410x.2006.06439.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment with darifenacin for overactive bladder: results of a 2‐year, open‐label extension study

Abstract: OBJECTIVE To examine, in a 2‐year, non‐comparative, open‐label extension study, the safety, tolerability and efficacy of darifenacin controlled‐release (CR) 7.5/15 mg once daily in patients with overactive bladder (OAB) who completed two 12‐week randomized, double‐blind, placebo‐controlled ‘feeder’ studies. PATIENTS AND METHODS Patients entering the extension received darifenacin 7.5 mg once daily for 2 weeks, after which a voluntary increase in dose to 15 mg was permitted. Thereafter, patients could adjust th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 18 publications
7
35
0
1
Order By: Relevance
“…However, most previous clinical studies focused on either of the two symptoms. [12][13][14][15] These studies provided limited information on the associated LUTS secondary to BPH in patients with storage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, most previous clinical studies focused on either of the two symptoms. [12][13][14][15] These studies provided limited information on the associated LUTS secondary to BPH in patients with storage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Self reporting of medication adherence includes direct questioning and use of validated questionnaires, e.g. the medication adherence report scale (MARS), used to measure adherence to medication in OAB [7,8] Patients might claim to adhere to therapy to avoid disapproval from clinicians Third party estimates of adherence tend to overestimate patients' adherence [9] Return unused medication…”
Section: Disease Factorsmentioning
confidence: 99%
“…There have been five longterm, open-label extensions of randomized controlled studies assessing adherence with oxybutynin, darifenacin tolterodine, solifenacin, and trospium [8][9][10][11][12]; the results are shown in Table 2.…”
Section: Disease Factorsmentioning
confidence: 99%
“…Withdrawals during the short-term registration RCTs were few, and the results of long-term or open-label extension studies have also shown very good long-term persistence, e.g., a 1-year continuation rate of 75% for trospium chloride [6], a 40-week continuation rate of 81% for flexible-dose solifenacin [7], a 1-year continuation rate of 71% for tolterodine extended-release [8], and a 2-year continuation rate of 66% for darifenacin [9]. However, the external validity of these findings has been questioned by the somewhat more somber findings of real-life prescription refill behavior.…”
Section: Introductionmentioning
confidence: 99%